An Empirical Test of Age-Graded Informal Social Control Theory: New Correlates of Youth Deviance. (February 2021) - Unlu, Ali; Ekici, Niyazi; Tasgin, Serkan; Entzminger, Phillip
This study examines several family structural variables that have a hypothesized effect on delinquency, substance abuse, and violence. We conducted a survey for potential correlates of Sampson and Laub's age-graded informal social control theory variables within the Turkish context. Our large sample size (31, 272), drawn from high school students in Istanbul, Turkey, allowed us to test the effects of family settings on youth deviance by using various statistical tests and programs. Our findings indicate that juveniles exposed to parental substance abuse are more likely to use illegal substances, commit a greater number of delinquent acts, and participate in more instances of violent behavior. Additionally, family social capital, residential mobility, religiosity, and the number of siblings were some other statistically significant correlates of delinquency.